2019
DOI: 10.18231/j.ijca.2019.117
|View full text |Cite
|
Sign up to set email alerts
|

Predicting difficult intubation: A comparison between upper lip bite test (ULBT) and Modified Mallampati test (MMT)

Abstract: No anaesthesiologist like to face scenario of unanticipated difficult intubation, as it may cost patients life. Many tests are there to predict difficult intubation, amongst those tests Modified Mallampati test [MMT] is a gold standard test. Upper lip bite test [ULBT] is an acceptable option for predicting difficult intubation. Our study aimed to compare both the tests to predict difficult intubation. Objectives: To analyse positive predictive value (PPV), negative predictive value (NPV), sensitivity, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…MMT: Patient was asked to sit up with his mouth open as much as possible and to stick out his tongue without making a sound. Oropharyngeal structures are visualized and classified with the help of a flashlight [ 8 – 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…MMT: Patient was asked to sit up with his mouth open as much as possible and to stick out his tongue without making a sound. Oropharyngeal structures are visualized and classified with the help of a flashlight [ 8 – 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Khan et al compared the ULBT and MMT and showed that the former was more accurate (88.7% versus 66.8%), while sensitivity, NPV, and PPV were similar in both tests [ 4 ]. A study conducted by Sinharay et al [ 21 ] observed that sensitivity (88.46%), PPV (71.87%), and NPV (97.45%) of ULBT were higher than MMT with similar specificity of both tests. Likewise, a study conducted by Ali et al [ 22 ] revealed that the sensitivity (87.5%), PPV (71.6%), and NPV (97.3%) of ULBT were higher than MMT with comparable sensitivity.…”
Section: Discussionmentioning
confidence: 99%